Development of biodiesel industry in China: Upon the terms of production and consumption. (February 2016) - Xu, Yang-Jie; Li, Guo-Xiu; Sun, Zuo-Yu
Abstract: The prices of primary energy have been ineluctably raised up due to the enormous energy consumption in China, and the economy suffers a lot from the severe energy shortage. Therefore, the necessity of using renewable energy in China is particularly important. Biodiesel has become one of the major renewable fuels of biomass energy. Since China׳s biodiesel industry just starts at the primary stage, improving the production capacity of biodiesel for meeting the soaring on energy demands is more necessary for the sustainable development in China. The materials for biodiesel production are various and sufficient in China, that indicates China could have a brilliant potentiality in the production capacity of biodiesel; however, whether such prediction could be true is still needed to be discussion in depth and further. For well answering the query, the development of biodiesel industry in China has been systematically reviewed upon the terms of production and consumption, and three essential aspects ('how to sufficiently take advantage of such plentiful feedstock for obtaining a satisfied production capacity', 'how to reasonably use such biodiesel in each region', and 'how to scientifically encourage the development of Chinese biodiesel industry') have been discussed. From the review and discussions, it can be concluded that the rising China׳s biodiesel industry is still behind the actual demand asked by 12th Five-Years Plan and continuous introduction of capitals is the effective method to a further development. Meanwhile, the development of China׳s biodiesel industry is highly depended on the raw materials whose sources and production capability are remarkably different in different regions, and hence make standards on the quality of biodiesel is essential and crucial to the further development. Furthermore, adjusting tax policies and forcing the application of biodiesel as addition to fossil diesel can effective establish and enlarge the market of biodiesel in China.